Physilogical role of Carnosine in contracting muscle - Begum, G.; Cunliffe, A.; Leveritt, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
High-intensity exercise leads to reductions in muscle substrates (ATP, PCr, and glycogen) and a subsequent accumulation of metabolites (ADP, Pi, H+, and Mg2+) with a possible increase in free radical production. These factors independently and collectively have deleterious effects on muscle, with significant repercussions on high-intensity performance or training sessions. The effect of carnosine on overcoming muscle fatigue appears to be related to its ability to buffer the increased H+ concentration following high-intensity work. Carnosine, however, has other roles such as an antioxidant, a metal chelator, a Ca2+ and enzyme regulator, an inhibitor of protein glycosylation and protein-protein cross-linking. To date, only 1 study has investigated the effects of carnosine supplementation (not in pure form) on exercise performance in human subjects and found no improvement in repetitive high-intensity work. Much data has come from in vitro work on animal skeletal muscle fibers or other components of muscle contractile mechanisms. Thus further research needs to be carried out on humans to provide additional understanding on the effects of carnosine in vivo.